2020
DOI: 10.3390/nano10091789
|View full text |Cite
|
Sign up to set email alerts
|

TinO2n−1 Suboxide Phases in TiO2/C Nanocomposites Engineered by Non-hydrolytic Sol–Gel with Enhanced Electrocatalytic Properties

Abstract: We report a non-hydrolytic sol-gel (NHSG) route to engineer original mesoporous TinO2n−1@TiO2/C nanocomposites. The synthetic approach is straightforward, solvent-free, additive-free, and meets the challenge of atom economy, as it merely involves TiCl4 and THF in stoichiometric amounts. We found that these nanocomposites present enhanced electrocatalytic properties towards the oxygen reduction reaction (ORR) in 0.1 M KOH. We believe that these preliminary results will open a window of opportunity for the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Xiao et al 29 studied Pt loaded on ZSM-5 with various Si/Al ratios and exchanged cations for toluene combustion; it was revealed that changing the Si/Al ratio can affect the quantity of metallic Pt and the hydrophobicity of the fabricated catalysts, which are the key factors influencing the activity. In another study by the same group, 30 they have demonstrated that the enhanced catalytic activity on Pt/NaZSM-5 for propene oxidation is closely related to the increased Si/Al ratios, which is favorable for propene adsorption. Hardacre et al 31,32 studied NO x -SCR with HC compounds (such as toluene) and alcohols.…”
Section: Introductionmentioning
confidence: 95%
“…Xiao et al 29 studied Pt loaded on ZSM-5 with various Si/Al ratios and exchanged cations for toluene combustion; it was revealed that changing the Si/Al ratio can affect the quantity of metallic Pt and the hydrophobicity of the fabricated catalysts, which are the key factors influencing the activity. In another study by the same group, 30 they have demonstrated that the enhanced catalytic activity on Pt/NaZSM-5 for propene oxidation is closely related to the increased Si/Al ratios, which is favorable for propene adsorption. Hardacre et al 31,32 studied NO x -SCR with HC compounds (such as toluene) and alcohols.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, the preparation of TiO 2 /C composites is an effective strategy to improve the gas sensitivity of NH 3 . TiO 2 /C composites have been synthesized by various methods, such as electrospinning, hydrothermal composite, solvothermal, and sol–gel carbonization. In these methods, TiO 2 /C composites are synthesized by first preparing TiO 2 and then combining the prepared TiO 2 with an additional carbon source to form a mixture, which leads to a long, time-consuming, and costly complexation process. Therefore, it is important to explore a simple and low-cost synthesis method to prepare TiO 2 /C.…”
Section: Introductionmentioning
confidence: 99%